2019
DOI: 10.1016/j.toxrep.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profile and in vivo toxicity evaluation of unripe Citrus aurantifolia essential oil

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…Terpenoids (such as carvone) have more antibacterial properties than terpenes, since terpenoids have functional group like hydroxyl which can scatter electrons, and so, promotes antimicrobial properties. Carvone and gama-terpinene belong to terpenes group with slight antimicrobial properties [[28], [29], [30], [31]]. A number of EO compounds which do not have health-risk have been registered by the European Commission for use as flavors in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids (such as carvone) have more antibacterial properties than terpenes, since terpenoids have functional group like hydroxyl which can scatter electrons, and so, promotes antimicrobial properties. Carvone and gama-terpinene belong to terpenes group with slight antimicrobial properties [[28], [29], [30], [31]]. A number of EO compounds which do not have health-risk have been registered by the European Commission for use as flavors in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of haematological biomarker thresholds forecasts the level of toxicity of the substance [ 22 , 24 ]. Moreover, haematological indicators in animal models are crucial for assessing toxicity concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, black caraway essential oil did not affect the immune, blood system, body enzymes and vital organs of the body [ 40 ]. On the other hand, Citrus aurantifolia EO showed mild hematotoxicity, nephrotoxicity and hepatotoxicity among the 100 mg/kg and 500 mg/kg dose groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thymus vulgaris L EO was well tolerated up to the dose of 2000 mg/kg in acute exposure, and the 28-day sub-acute toxicity study revealed that the no-observed-adverse effect level (NOAEL) was greater than 250 mg/kg/day [ 54 ]. Citrus aurantifolia posed mild hematotoxic, nephrotoxic and hepatotoxic effects in doses of 100 mg/kg and 500 mg/kg in 60-day repeated dose study [ 41 ]. Mild toxicity observed in the latter case could be attributed to longer treatment; 28 days versus 60 days.…”
Section: Discussionmentioning
confidence: 99%